The Correlation Between Primary Student’s Snacking Pattern and Physicial Activity with Their Glucose Level in Makassar - Hardiani, Hardiani; Syarfaini, Syarfaini; Syahrir, Sukfitrianty; Syarif, Alwiyah Nur (Diversity: Disease Preventive of Research Integrity, 2020)
Diabetes mellitus (DM) has become a prevalent problem in Indonesia as indicated by an estimated number of 240 cases per year from a total of 83 million children population. Obese children have a 10.25 higher risk for developing a high level of glucose compared to those with normal nutritional status. This research particularly focuses on investigating the correlation between primary student’s snacking pattern and physical activity with their glucose level at Islamic Primary School Athirah in Makassar by adopting a cross-sectional study research design. The samples were selected from the population of obese students with a percentage of n=32 by utilizing the purposive sampling technique. Some instruments such as consent letters, Seca Weight Scale, blood glucose level checker Microtoise, and FFQ questionnaires were used to collect research data. To measure the correlation between variables, this research used the Chi-Square test. The findings suggest that there is a correlation between a primary student’s snacking pattern and their blood glucose level (p=0.043). The findings also indicate that the student’s physical activity correlates with their blood glucose level (p=0001). To conclude, through the findings, this research encourages parents to be more apprehensive of their children's snacking behavior and physical activities, so that diabetes mellitus can be prevented as early as possible.